Implementasi Metode Fuzzy AHP untuk Sistem Pendukung Keputusan Peminjaman pada Koperasi Kredit Sejahtera - Muhammad Galih Wonoseto; Muhammad Yolan Alfiandy (Jurnal Sistem Informasi Bisnis, 2023)
Koperasi Kredit Sejahtera is a cooperative engaged in savings and loan services in the Bogor area. One form of KKS service to employees is by providing loan funds to help solve financial problems for employees. The problem faced by KKS so far is that decision-making activities in lending are still inadequate which results in non-performing loans or bad debts because the cooperative does not have a special system for decision making. Based on the problems that occur, researchers will build a decision support system that can handle credit problems using the Fuzzy AHP method using 9 criteria, namely salary, term, other loans, membership status, expenses, accuracy of previous payments, work, loan purpose and loan amount so that it can help the cooperative in determining the provision of loans to prospective creditors quickly, precise and accurate according to the ranking of the fuzzy AHP calculation results. Blackbox testing is carried out to test the achievement of the functional requirements of the system which shows that the functional requirements are met 100% of the total 8 functional consisting of 5 functional on admin actor and 3 functional on officer actor can be done/valid. UAT testing is used to test the achievement of non-functional requirements. By conducting a questionnaire to 16 respondents, the result is 100% valid and reliable. So that 100% of non-functional needs are successfully met.